Experimental and numerical analysis of a masonry wall under hydrostatic and debris impact loads - Korswagen, Paul A.; Bricker, Jeremy D.; Jonkman, Sebastiaan N.; Kolen, Bas (Frontiers in Built Environment, 2025)
The structural response of masonry walls during flood events is a critical concern for the flood resilience of (Dutch) buildings, as they typically constitute part of the load-bearing structure. This study investigates the out-of-plane behaviour of a full-scale single-wythe fired-clay-brick masonry wall under out-of-plane hydrostatic pressure and debris impact loads. Experimental tests were conducted on a 2.7 × 2.7 m masonry wall subjected to a vertical pre-compression and simultaneously varying water levels and debris impacts at the Flood Proof Holland facility in Delft, the Netherlands. Results demonstrated that the wall remained within the linear-elastic regime up to a water depth of approximately 90 cm when the interior side was dry. Beyond this threshold, crack initiation and stress redistribution occurred, leading to significant deformation. On the basis of calibrated models, failure was predicted at approximately 150 cm water depth for a fully restrained wall. Debris impact tests showed that soft debris, represented by a floating log, caused negligible additional damage, whereas repeated impacts with a steel cube (hard debris) resulted in progressive cracking and local failure, particularly at higher water levels. Numerical models, including analytical, linear-elastic finite element method (FEM), and non-linear FE approaches, were calibrated using the experimental data. While one-way bending models predicted conservative failure thresholds, two-way, non-linear models accurately captured the wall’s deformation and cracking behaviour, demonstrating the importance of lateral boundary constraints in determining wall capacity and stability. The findings emphasise that traditional masonry walls in Dutch buildings can safely withstand water depths up to 90 cm without significant damage. However, higher water levels or hard debris impacts pose substantial risks, highlighting the need for improved flood resilience strategies. Future work should focus on cavity wall systems, leakage effects, and the behaviour of walls with openings.